Effect of Garlic Powder Supplementation on Total Cholesterol and Low Density Lipoprotein Level in Patient with Hypercholesterolemia: A Meta-Analysis - Zulkarnain, Zuraida; Dewi, Yulia Lanti Retno; Murti, Bhisma (Indonesian Journal of Medicine, 2022)
Background: Hypercholesterolemia is a risk factor for cardiovascular disease that can cause death and disability, so it must be managed properly. Garlic flour (GP) is one of the dosage forms of garlic that has the potential to reduce cholesterol. This study is a systematic review and meta-analysis that aims to determine the effectiveness of GP in reducing total cholesterol (TC) and low density lipoprotein (LDL).Subjects and Method: Search articles through the Pubmed database, Google scholar, Proquest, Springer link, and Science direct with the appropriate keywords. Population= patients with hypercholesterolemia. Intervention= GP. Comparison= placebo. Outcome= TC and LDL. Inclusion criteria included complete articles in English or Indonesian published from 2010-2022, Randomized Controlled Trial (RCT) design, subjects >18 years old with hypercholesterolemia, the study had a complete fat profile outcome, duration of intervention 2 weeks-12 months. The flow of article selection is based on the PRISMA flow diagram. Meta-analysis using RevMan 5.3 with effect size standardized mean difference (SMD) and Random Effect Model (REM) analysis model.Results: A total of 10 articles were eligible for a meta-analysis. The GP group had TC levels 1.49 units lower than the placebo group (SMD = -1.49; 95% CI = -1.95 to -0.55; p = 0.005) and LDL levels 0.68 units lower than the placebo group (SMD= -0.68; CI95). %= -1.08 to -0.27; p=0.001). Subgroup analysis based on the length of the intervention showed that administration of GP <12 weeks only significantly reduced TC while administration > 12 weeks significantly reduced TC and LDL.Conclusion: GP is effective in lowering TC and LDL especially at 12 weeks or more.Keywords: garlic powder, hypercholesterolemia, RCTCorrespondence: Zuraida Zulkarnain. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126. Mobile: 081393933862. Email: zuraida.zu@gmail.com.Indonesian Journal of Medicine (2022), 07(01): 102-114https://doi.org/10.26911/theijmed.2022.07.01.11